Development of pump control system for acoustic integration chips - Koh, Gregory Boon Leong (2018)
This report provides an in-depth insight into my final year project on developing a pump control system for the integrated acoustic chip. It gives a brief introduction of the project and the development phases it had went through before the whole system was established and tested out in actual experiment. The third chapter focuses on the development of the peristaltic pump system. It provides a description on the structure of the pump and the parameters that was selected into the system. Next, it covers the hardware that was essential to operate the system, the software that was required to control the operation of the pump and the function that was added into the system required for the experiment. The forth chapter covers the development of the syringe pump. It lists out the missing functions of the pump controller that was given by manufacturer. Enhancement has been done to improve the system. Lastly, the steps to test the system reliability. The fifth chapter narrows down to the integration of the pump system. Firstly, it tests out the functionality to prove that both pump could work simultaneously. After which, disadvantages were listed out and further improvisation was done to remove it. Additional features were added into the system controller so that user could monitor the experiment. The sixth chapter explains about the platform that was being built and designed. Its purpose was to mount all the components up so that user could easily carry the system within the lab to conduct experiment. Component was replaced so that everything could be mount. Finally, the pump control system was integrated with the chip and was used to test out in the experiments. Recommendation was discussed for future enhancement in the system.